Analisis Pengalaman Pengguna pada Website Kampus Merdeka menggunakan Metode UX Curve - Muhammad Raihan Agust Nugroho; Hanifah Muslimah Az-Zahra; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Kampus Merdeka is a program that was created by the ministry of education cultural, research and technology of Indonesia on 2020 to facilitate the learning progress for student outside campuss environment. The ministry also launched a website to simplify the administration process and to monitor student's activity. This study aims to analyze the user experience in the Kampus Merdeka's website using UX Curve method. UX Curve method has 3 phase initial questionnaires, curve drawing templates, and final questionnairess. Initial questionnaire' function is to collect participant's demography data, curve drawing templates is the drawing phase, and final questionnairess is the last phase to complete the score, and user's perception of the website. From the data gathered on 10 participant it generate 40 curves, from 4 different UX dimension which is general UX, attractiveness, utility, and ease of use. Beside the curves there are 51 reasons consist of positive and negative factors, that will be categorized to pragmatic and hedonic factors. According to the result from this study factor that influence the user experience in the Kampus Merdeka's website are the interface is simple, the website is easy to use, and the enrollment process is difficult.